Environmental standard readings for manuscript artifacts in display case at Terengganu State Museum and ‘First Galleria’ Taiping / Norashikin Abdul Karim ... [et al.] - Abdul Karim, Norashikin; Talib, Anuar; Sujak, Ilyana; Abd Rashid, Mohd Sabrizaa (2012)
Manuscript artifacts in a museum‟s display case will usually undergo a process of deterioration. This type of artifact is categorized into „sensitive artifacts‟. Due to the organic contents in these sensitive artifacts, extra supervision are required. Manuscript artifact easily react to the heat, humidity and Lux. Standard guidelines for temperature, humidity and Lux reading was introduced by an international agency, ICOM (International Council of Museum) to ensure the preservation of these categories of artifacts. This paperwork intended to discuss how far the implementation of the guidelines to Malaysian museums.The finding reveals that most of manuscript artifacts are contravened with the guideline.